Ensuring data integrity in industrial Internet of Things systems using error-correcting codes - Yevheniev, A.M.; Sydorenko, Z.M.; Sievierinov, O.V. (Radiotekhnika, 2025)
The article explores the challenges of ensuring data integrity and error resistance in Industrial Internet of Things (IIoT) systems, which are critically important for the functioning of automated manufacturing processes. A comprehensive analysis of key IIoT security issues is presented, along with an overview of current data protection approaches. The focus is placed on the use of error-correcting codes, particularly Goppa codes, which demonstrate high efficiency in detecting and correcting errors and show strong potential for integration into cryptographic systems. It is shown that Goppa codes can ensure not only error resistance but also data integrity due to the vast number of encoding rules, making them suitable for use in post-quantum cryptography scenarios. The results demonstrate that using Goppa codes allows for the preservation of data integrity and a significant reduction in the likelihood of introducing false data while maintaining the required level of error resistance. This confirms the feasibility of integrating such codes into the IIoT environment.